Central Diabetes Insipidus in an Extremely-Low-Birth-Weight Preterm Infant with Suspected Ectopic Posterior Lobe of the Pituitary Gland - Yung Zu Park; Inseong Hwang; Sung-Ha Kim; Sook Min Hwang; Tae-Jung Sung; Hye Jin Lee (Korean Society of Neonatology, 2020)
Central diabetes insipidus (CDI) is extremely rare in neonates, especially in extremely-low-birth-weight infants, and most cases are secondary to conditions, such as ischemic or hemorrhagic brain damage. Here, we report a case of CDI in a 530-g infant born at 23+3 weeks of gestation, with suspected ectopic posterior pituitary gland. Hypernatremia was noticed at 33+6 weeks of postmenstrual age, and it persisted with in creased volumes of diluted urine, despite adequate sodium intake. Serum and urine osmolality returned to the normal range after administration of a desmopressin injection. The bright spot of the posterior pituitary was absent, and brain magnetic resonance imaging suggested an ectopic posterior pituitary gland. At the time of writing this manuscript, the patient was on oral desmopressin medication without complications at the corrected age of 8 months. Through this report, we emphasize that although CDI is extremely rare in premature infants, it should be suspected when hypernatremia and polyuria that are unexplained by other causes are noted.